Influence of age on outcomes in prolonged weaning from mechanical ventilation - Michels-Zetsche, Julia D.; Röser, Evelyn; Ersöz, Hilal; Neetz, Benjamin; Dahlhoff, Jana C.; Joves, Biljana; Trinkmann, Frederik; Höger, Philipp; Kontogianni, Konstantina; Weissmann, Cornelia; Barre, Max; Fähndrich, Sebastian; et al. (BMJ Open Respiratory Research, 2025)
Background Older age has been identified in many studies as a predictor of poor outcomes in intensive care, including weaning failure. Age is a risk factor for prolonged weaning, resulting in an increased number of geriatric patients being referred to specialist weaning centres. The aim of our analysis was to investigate weaning outcomes in different age groups.Methods We analysed patients in prolonged weaning at Thoraxklinik Heidelberg from 1 December 2008 to 31 December 2023. We classified three groups: ≤64, 65-79 and ≥80 years of age. The patients’ characteristics and weaning success, as well as weaning failure (continued invasive mechanical ventilation (IMV) and death), were analysed using group comparisons and logistic regression analyses.Results During the study period, 915 patients (64.9±13.7 years, 39.3% female) underwent prolonged weaning. 73.3% were successfully weaned, 20.2% were discharged with IMV and 6.6% died. 40.5% of the patients were ≤64 years, 49.7% were 65-79 years and 9.7% were ≥80 years old. There was a significant difference in weaning success: in the group ≤64 years the success rate was 79.0%, 65-79 years 70.3% and ≥80 years 64.0%, p=0002. The patients’ characteristics differ in the age groups, with more postoperative patients, delirium and cardiovascular comorbidities and less neuromuscular disease and malignancy in ≥80 years old patients.Conclusions 64% of carefully selected patients ≥80 years of age could be successfully weaned in a specialised centre instead of being discharged from a general intensive care unit with continuing IMV in an outpatient intensive care setting.
Gesehen am 15.09.2025